Monitoring heart rate during acclimatization in women - Jereb, B.; Burnik, S. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Adaptation of human organism to higher altitudes is called acclimatization. All mountain climbers that climb the mountains at higher altitudes have to face it. A period of acclimatization ranges between one and three weeks. It varies from person to person, and depends on the altitude this person wants to reach. The higher one climbs, the longer acclimatization one needs. The processes of adaptation to higher altitudes can be monitored by means of various physiological parameters, i.e. heart rate, pulse volume, blood pressure, use of oxygen, and other biochemical variables. Monitoring of most of these variables is limited to laboratory measurements, due to objectivity of measuring methods. As a rule, heart rate in rest increases with altitude until it reaches a certain value at which it remains more or less constant. On the other hand, maximal heart rate under the same load decreases with the increase in altitude. In the field, however, the results are somewhat different. Our purpose was to monitor heart rate changes in real conditions, on a climbing tour, with different acclimatization periods. We also wanted to determine its value for acclimatization level assessment in mountaineering and mountain climbing at high altitudes. Methods: Sample group Our group of subjects consisted of 6 healthy women (age 25±4,7, height 165,2±6, mass 61,4±7,4), who were beforehand well acquainted with the test. Description of the test Measurements were taken at two different altitudes. First measurement was taken before the departure to a trekking tour in Ljubljana at an altitude of 300 m, and then twice in Huaraz at an altitude of 3200 m. The first acclimatization tour lasted for 8 days and was followed by measurements; the second acclimatization tour lasted for 4 days and was again followed by measurements (Figure 1). Heart rate was measured by means of Polar measuring devices in rest (sitting position) and in active state (step test on a 20 cm high stepper). Step test • 3 min of rest (sitting on the stepper), • 5 min of step test with a frequency of 60 Hz, • 3 min of rest (sitting on the stepper), • 5 min of step test with a frequency of 80 Hz, • 3 min of rest (sitting on the stepper). Data analysis Data were processed with SPSS for Windows software: Basic statistical parameters were calculated for each variable. For a comparison of the variables within one measurement t-test for independent samples was used. For a comparison of variables among the measurements variance analysis and t-test were used. Results (see figures) Discussion: The results show (Figure 2) statistically significant differences of average heart rates in rest between Ljubljana and Huaraz 2. In Huaraz 1, however, no differences were shown. Heart rates in Ljubljana and Huaraz 1 are somewhat lower during the second acclimatization period, which shows that the acclimatization period was long enough for heart rates to drop from the values reached in active state to rest values. Average heart rate after 80 Hz step test show statistically significantly higher values (Figure 2) than it does after 60 Hz step test. This was an expected outcome, as the intensity at 80 Hz is a little higher than the intensity at 60 Hz, and in consistence with the results of other research. Heart rate in rest varies significantly between the groups (Figure 3) in almost all cases. Differences did not appear only during the first acclimatization period in Huaraz 2. It is surprising that average heart rate in rest does not increase in higher altitudes. Moreover, much lower average heart rates were measured in Huaraz 1 than in Ljubljana (Figure 3). Similar heart rate differences during acclimatization were measured by Pavlidis et al. (2005) and Mazzeo et al. (1998) in their research. Increase in average heart rate in accordance with increase of altitude was measured by researchers that took measurements in hypobaric chamber. Similar results were obtained by Antezana et al. (1994) during her laboratory measurements at an altitude of 6,542m. As we did not measure other physiologic parameters we can not explain this difference between two measurements at the same altitude. According to our opinion, the differences are due to not only inconsistent weather conditions during our measurements. Differences in average heart rate were measured also during step tests. The results show differences similar to those measured during acclimatization periods. The lowest values were measured in Huaraz 1 (Figure 3). The work load of step tests with 60 Hz and 80 Hz was not strong enough to enable us to measure maximal heart rate. The maximal heart rate decreases with higher altitudes. Conclusions: We are aware of the drawbacks of field measurements. Changes in heart frequency are influenced by numerous factors, which depend on environmental factors, such as weather conditions. Additional measurements will have to be taken before heart rate measured in the field can be used for the assessment of the rate of acclimatization for mountaineering and mountain climbing in higher altitudes.